Three new isobenzofurans from the roots of Nicotiana Tabacum and their bioactivities. Issue 23 (2nd December 2017) - He, Pei; Yang, Peisong; Tang, Shiyun; Ye, Ling; Liu, Chunbo; Shen, Qinpeng; Tang, Dangyu; Zhang, Fengmei; Liu, Zhihua; Chen, Yongkuan; Yao, Shouzhuo; Xiang, Nengjun; et al.
Abstract: Three new isobenzofurans (1–3 ), together with four known phenylpropanoids (4–7 ) were isolated from the roots of Nicotiana tabacum . Their structures were determined by means of HRESIMS and extensive 1D and 2D NMR spectroscopic studies. Compounds1–6 were tested for their anti-tobacco mosaic virus (anti-TMV) activities and cytotoxicity activities. The results showed that compounds5 and6 exhibited high anti-TMV activities with inhibition rates of 35.1 and 33.4%, respectively. The cytotoxicities of compounds1–7 against five human tumor cell lines (NB4, A549, SHSY5Y, PC3 were also tested. Compounds1–7 showed weak inhibitory activities against some tested human tumor cell lines with IC50 values in the range of 3.8–9.6 μM. Abstract :